Rhodium(I) Complexes as Useful Tools for the Activation of Fluoroolefins - Talavera, María; Braun, Thomas (Synlett, 2020)
In this account we describe studies on the reactivity of rhodium(I) complexes of the type [Rh(E)(PEt3)3], where E represents hydrido, fluorido, germyl, boryl or silyl ligands, towards fluorinated olefins. The results are compared with those reported by other research groups on fluoroolefins, as well as with the chemistry of compounds [Rh(E)(PEt3)3] towards fluoroaromatics in terms of selectivity and mechanisms.1 Introduction2 Reactivity Towards Fluoroolefins2.1 Reactivity of Hexafluoropropene2.2 Reactivity of (E)-1,2,3,3,3-Pentafluoropropene2.3 Reactivity of 2,3,3,3-Tetrafluoropropene and (E)-1,3,3,3-Tetrafluoropropene2.4 Reactivity of 3,3,3-Trifluoropropene2.5 Reactivity of Pentafluorostyrene3 Conclusion and Perspective
Keywords: rhodium; fluoroolefins; C–H bond activation; C–F bond activation; borylation; silylation; germylation; hydrodefluorination